Towards Low-Cost Tangible Extended Reality for Mathematics Education - M. de Moraes, Leonardo; G. Souto, Gustavo; Morimoto, Carlos Hitoshi (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: Math anxiety is a common challenge for young students, often impairing learning and engagement. Tangible and extended reality (XR) technologies offer opportunities to make learning more interactive, collaborative, and less intimidating. Objective: This work proposes XR4Math, a low-cost tangible XR system designed to reduce math anxiety through personalized and engaging activities. Methodology: The system synthesizes principles from embodied cognition, collaboration, and multimodal design. Results: We demonstrate its potential through two proof-of-concept applications: ExpressionXR, a tangible game for solving arithmetic expressions, and PuzzleXR, a geometric construction puzzle.